2017
DOI: 10.3892/ol.2017.6833
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous DKK‑3/REIC inhibits Wnt/β‑catenin signaling and cell proliferation in human kidney cancer KPK1

Abstract: Abstract. The third member of the Dickkopf family (DKK-3), also known as reduced expression in immortalized cells (REIC), is a tumor suppressor present in a variety of tumor cells. Regarding the regulation of the Wnt/β-catenin signaling pathway, exogenous DKK-1 and DKK-2 are reported to inhibit Wnt signaling by binding the associated effectors. However, whether exogenous DKK-3 inhibits Wnt signaling remains unclear. A recombinant protein of human full-length DKK-3 was used to investigate the exogenous effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…We conducted a dose response analysis for each selected bone-secreted factors. We used factor concentrations reported in the literature 4147 and tested several concentrations to ensure that the dosages used do not cause toxicity, i.e., cell death, in PCa cells using live-cell imaging. Based on the response, we selected the following concentrations for further study: DKK3 (10 µg/mL), BMP1 (0.4 µg/mL), vasorin (0.25 µg/mL), neogenin (0.5 µg/mL), MIA (0.1 µg/mL), or NGAL (0.25 µg/mL) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a dose response analysis for each selected bone-secreted factors. We used factor concentrations reported in the literature 4147 and tested several concentrations to ensure that the dosages used do not cause toxicity, i.e., cell death, in PCa cells using live-cell imaging. Based on the response, we selected the following concentrations for further study: DKK3 (10 µg/mL), BMP1 (0.4 µg/mL), vasorin (0.25 µg/mL), neogenin (0.5 µg/mL), MIA (0.1 µg/mL), or NGAL (0.25 µg/mL) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the high factor concentrations used in our studies are within the range reported in the literature. As an example, similar concentrations of human DKK3 at 10–50 µg/mL were used to block the proliferation of human kidney KPK1 cancer cells 41 ; human BMP1-3, an alternatively-spliced variant of BMP1, at 150–1000 ng/mL was observed to increase the expression of p21, a cell cycle inhibitor, in human embryonic kidney 293 (HEK293) cells 42 ; human MIA at 50 ng/mL was used to inhibit the invasive activity of melanoma cells 45 ; and PEDF at 250 ng/mL was used to induce osteoblastic differentiation of human mesenchymal stem cells 47 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 65 ] The involvement of DKK3 in modulation of Wnt‐signaling has been extensively described. [ 27 , 28 , 66 ] As simple GSEA is frequently hampered in discriminating the repression or activation of a given pathway, we determined differentially regulated genes (DEG) at individual time points. [ 67 ] In line, the amount of DEGs increased over time with highest numbers at 96 h after induction of pancreatitis (Figure 6F ), an observation in concordance with our morphological observations.…”
Section: Resultsmentioning
confidence: 99%
“…[20,65] The involvement of DKK3 in modulation of Wnt-signaling has been extensively described. [27,28,66] As simple GSEA is frequently hampered in discriminating the repression or activation of a given pathway, we determined differentially regulated genes (DEG) at individual time points. [67] In line, the amount of DEGs increased over time with highest numbers at 96 h after induction of pancreatitis (Figure 6F), an observation in concordance with our morphological observations.…”
Section: Dkk3 Loss Limits Canonical Wnt-signaling During Pancreatic Regenerationmentioning
confidence: 99%